Paracoccidioidomycosis mortality in Brazil (1980-1995) - Coutinho Ziadir Francisco; Silva Delson da; Lazéra Márcia; Petri Valéria; Oliveira Rosely Magalhães de; Sabroza Paulo C.; Wanke Bodo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This study analyzes 3,181 deaths from paracoccidioidomycosis in Brazil, based on 16 years of sequential data (from 1980 to 1995). During this period paracoccidioidomycosis showed considerable magnitude and low visibility, representing the eighth most common cause of death from predominantly chronic or recurrent types of infectious and parasitic diseases. It also had the highest mortality rate among the systemic mycoses. The mean annual mortality rate was 1.45 per million inhabitants, indicating a downward long-term trend (reduction of 31.28%), while spatial distribution among the different regions and States of Brazil was non-homogenous. The South (with the highest regional rate) and the Southeast showed a downward trend, while the Central West had the second highest rate in the country. At least one-fifth of Brazilian municipalities (or 22.71% of the country's total area) reported deaths from paracoccidioidomycosis. Overall nationwide mortality per area was 3.73/10,000km². The disease was endemic in non-metropolitan areas. The majority of deaths occurred in males (84.75%), and there was a sex ratio of 562 men/100 women. The 30-59-year and over-60-year age groups were the most affected. The study showed that the mortality rate justifies classifying this disease as a major health problem in Brazil.